Electromagnetic design and optimization of ropeless overspeed protection device for direct drive elevators - Xu, Xiaozhuo; An, Jinsheng; Du, Baoyu; Feng, Haichao (AIP advances, 2025)
In response to the urgent need for safety protection devices in linear motor cordless elevators, a novel cordless overspeed protection device is proposed. It utilizes the eddy current force between the permanent magnet and the induction plate as the driving force. In addition, it automatically increases the coupling area in case of overspeed to achieve reliable safety protection, analyzes the topological structure and the working mechanism of the novel cordless overspeed protection device; establishes an analytical model of the permanent magnet eddy current force; and analyzes the influence relationships between the eddy current force and the operating speed, air gap length, permanent magnet parameters, and induction plate material. Subsequently, a sensitivity analysis was conducted using the finite element method, a response surface optimization model was established, and the RIME algorithm was combined to perform multi-objective optimization on key parameters. The results show that the overspeed protection device meets the design requirements and provides an important reference for the safety design of linear motor cable-free elevators.